The Universality of Luqman al-Hakim's Commandments and their Impact on the Individual, Family and Society - Naeim Ali, Mansour (Journal of College of Education, 2022)
The Qur’anic discourse is distinguished by the diversity of its rhetorical methods, which attract the contemplator to it. The answer to these texts finds that they are characterized by generality and comprehensiveness, and they were not limited to his son Luqman only. Working with them brings great benefit to all creation. Without excluding any human being, these commandments have become a constitution that enhances the cohesion, prosperity, development and victory of society in this world and the hereafter, through an analytical study of the Qur’anic texts that contain these blessed commandments.
Keywords: Luqman the wise; goodness of society